Palindromic Thinking in Contemporary Composition: Creative Techniques and Aesthetic Implications - Haiyue Wang; Lee Chie Tsang Isaiah (INSAM)
The aim of this research is to investigate the meaning of the palindrome in the musical work Huiwen, with a focus on its form of performance and composition, as well as the concept of the palindrome itself. In order to clarify and deepen the understanding of the palindrome in compositional writing, this study intends to explore and analyze the use of the palindrome in various compositional domains, ultimately explaining the musical compositional significance of this technique. Chapter One provides a detailed examination of the palindrome and its relation to similar concepts, including repetition and ambiguity. Chapter Two examines the implications of the palindrome’s involvement in different areas of composition, demonstrating its close association with physical meanings and creative intentions. Chapter Three discusses the musical work Huiwen and its use of the palindrome in detail, focusing on the various forms of palindrome within and between the parts. In conclusion, this study highly the unique function and influence of the palindrome in music in that it requires the composer to seek out and understand the specific forms and derived meanings of the palindrome in order to achieve abstraction based on existing concepts.